Using Video to Give More Effective and Engaging Science Talks - Brennan, Eric B. (Frontiers in Communication, 2021)
Science presentations at conferences are an important way that scientists share exciting research discoveries. Some presentations are informative and engaging, but unfortunately many are not. This article describes a novel method (Video Let’s Talk, VLT) for more engaging and effective science presentations, where the presenter 1. makes a video that fills half of the presentation time, 2. shows the video in lieu of a live presentation, and 3. spends the remaining time engaging with the audience. The benefits and challenges of the VLT method are described along with tips on how to do the VLT well. These insights are based on the author’s experience giving numerous VLT presentations to scientists, farmers and other groups over the past seven years. The VLT method is timely considering how the COVID pandemic has forced scientists to learn new skills in do it yourself (DIY) video making in order to participate in virtual conferences.